2011
DOI: 10.1002/jcb.23340
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between PKR and PACT mediated by LPS‐inducible NF‐κB in human gingival cells

Abstract: The double-stranded RNA-dependent protein kinase (PKR) is a serine/threonine kinase expressed constitutively in mammalian cells. PKR is activated upon virus infection by double-stranded RNA (dsRNA), and plays a critical role in host antiviral defense mechanisms. PKR is also known to regulate various biological responses, including cell differentiation and apoptosis. However, whether PKR is involved in the progress of periodontitis is not clear. The present study explained the phosphorylation of PKR by LPS in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…So, we also focused on the LPS and TLR4 systems in LX-2 cells. It is known that LPS treatment upregulates PACT expression [ 41 ], but we did not observe any differences in miR-122 expression between HSCs treated with or without LPS (1.1 or 1.0-fold, respectively).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…So, we also focused on the LPS and TLR4 systems in LX-2 cells. It is known that LPS treatment upregulates PACT expression [ 41 ], but we did not observe any differences in miR-122 expression between HSCs treated with or without LPS (1.1 or 1.0-fold, respectively).…”
Section: Discussioncontrasting
confidence: 79%
“…PACT is activated by bacterial products and cellular stress [ 40 ]. Yoshida et al [ 41 ] have reported that PACT-PKR interaction and phosphorylation of PKR are associated with the induction of NF-κB by LPS. Treatment of PKR inhibitor C16 prevented activation of NF-κB [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of PKR in inflammation appears to be dependent on both context and cell type (Yoshida et al. ; Watanabe et al. ).…”
Section: Introductionmentioning
confidence: 99%